STRATEGI PENGEMBANGAN DIRI SISWA MELALUI LAYANAN BIMBINGAN KONSELING DI MTs NEGERI BARENG JOMBANG - Ida Munawaroh; Sayidah Afyatul Masruroh; Ahmad Fakhruddin Fajrul I; Irhas Nur Abdillah; Ibnu Salamah (Menara Tebuireng, 2022)
The resreach problems are the focus of research is How a strategy of self-development at MTs Together, What is the role of counseling in MTs Together and What are the factors supporting and inhibiting factors in the strategy of self-development through guidance counseling in Together MTs Jombang. The aim of this study was describe the strategy of self-development through guidance and counseling services at MTs Together Jombang, Mendirkripsikan kegitatan role of counseling in personal development in Jombang and MTs Together To describe some of the factors supporting and inhibiting factors in the strategy of self-development through guidance and counseling services. This study used a qualitative approach because this research data around the globe. Source of data in this study a person of data that include, Principals, teachers, teacher BK, as well as non-person. The method used to obtain data on methods of observation, interviews and documentation. Sedangtkan data analysis technique, researchers first gather data, then the data is processed and presented using descriptive analytic method.From the research that researchers are (1) Strategy implementation guidance and counseling services in implementing the program of self-development is done in MTs Together is the strategy of basic services, strategy services responsive, Strategies individual planning and support system, (2) Role of Guidance and Counseling in Together MTs is Professor counseling as a change (change agents) and a Master of Guidance and Counseling As Integrator. (3) Media Development Supporting factors are self-sufficient, spirit teachers in exploring the potential, interests and talents of students, Instrumentation Data available, existence of special activities, such as visits to the homes of students. While the self-development program Obstacles Through Counseling Services in Jombang Together MTs are shortages of guidance at the school, at the school guidance technical ability, limited Infrastructures, organization and administration of guidance and supervision guidance in Madrasah.